A review of the optically and thermally stimulated luminescence properties of aluminosilicates - S.W.S. McKeever (Optical Materials: X)
This paper reviews the main literature describing models for thermoluminescence (TL), optically stimulated luminescence (OSL) and radiophotoluminescence (RPL) in aluminosilicate materials, namely natural feldspar minerals and synthetic glasses. The work examines the different models proposed to explain the various luminescence phenomena and compares them with each other. The models include thermally and optically stimulated excited-state tunneling, band-tail state hopping, and ionization and transportation through the band-tail states and/or the conduction band. Temperature and stimulation wavelength are critical parameters, with one model or another dominating over different temperature and/or wavelength ranges. Some recommendations for future research are noted.